Hubungan Homesickness dengan Kesehatan Mental Mahasiswa Perantau : Studi Literatur - Putri Rahayu; Silva Anugrah Febrina; Wita Dwi Anjani; Sri Mulyeni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Migrant students often face significant emotional challenges when transitioning to a new academic and living environment. One prominent issue is homesickness, which can disrupt emotional balance and impact overall mental health. In this context, homesickness is not only associated with feelings of longing for home and family but also affects psychological stability and the ability to adapt to new environments. This article aims to synthesize research findings on the relationship between homesickness and mental health among migrant students, with a focus on the higher education context in Indonesia. A literature review was conducted by searching Google Scholar, Garuda, DOAJ, and ERIC using the keywords "homesickness", "migrant students", and "mental health" (2019-2025). Relevant articles were selected based on specific criteria, and their findings were synthesized thematically. The reviewed literature consistently indicates that higher levels of homesickness are associated with increased stress, anxiety, depressive symptoms, loneliness, and reduced academic motivation. However, several protective factors can help mitigate the negative impact of homesickness, including social support from peers and family, effective Coping strategies, active participation in campus activities, and adaptive emotion regulation. Therefore, universities should provide various programs to support migrant students' psychological adjustment, such as early-semester orientation, peer mentoring, and easily accessible counseling services.